Profesi Tenaga Bimbingan dan Konseling yang Bermartabat - I Made Olas Astawa (UHN IGB Sugriwa Denpasar, 2015)
Consultancy and counselling services are helps provided to individuals in order that they become personalities with insight, view, skill that they are valuable in the societies. The Indonesian Government Regulation Nomor 20/ 2003 on the National Education System correctly states that councellors are educators, which means that those with the profession should produce work with high quality that they could develop students’ potentialities to reach success, both formally and socially. The works of a councellor depends on their qualification and competences that they gain from credible institutions. A councellor should be licensed and certified to indicate that he (she) has completed his (her) professional study and has been tested according to certain criteria given by a representative professional organisation or agency. This should be also supported with (1) dignity service, (2) tasked jobs, (3) healthy environment. These three can guarantee the maintenance of the professions.